From 2D to 3D: Promising Advances in Imaging Lung Structure - Klouda, Timothy; Condon, David; Hao, Yuan; Tian, Wen; Lvova, Maria; Chakraborty, Ananya; Nicolls, Mark R.; Zhou, Xiaobo; Raby, Benjamin A.; Yuan, Ke (Frontiers in Medicine, 2020)
The delicate structure of murine lungs poses many challenges for acquiring high-quality images that truly represent the living lung. Here, we describe several optimized procedures for obtaining and imaging murine lung tissue. Compared to traditional paraffin cross-section and optimal cutting temperature (OCT), agarose-inflated vibratome sections (aka precision-cut lung slices), combines comparable structural preservation with experimental flexibility. In particular, we discuss an optimized procedure to precision-cut lung slices that can be used to visualize three-dimensional cell-cell interactions beyond the limitations of two-dimensional imaging. Super-resolution microscopy can then be used to reveal the fine structure of lung tissue’s cellular bodies and processes that regular confocal cannot. Lastly, we evaluate the entire lung vasculature with clearing technology that allows imaging of the entire volume of the lung without sectioning. In this manuscript, we combine the above procedures to create a novel and evolutionary method to study cell behavior ex vivo, trace and reconstruct pulmonary vasculature, address fundamental questions relevant to a wide variety of vascular disorders, and perceive implications to better imaging clinical tissue.